Women's Shaf in Prayer Congregation and Wisdom (Philosophical Study of Fiqh Madzhab) - Asif Trisnani; Moh. Henri; Sujiat Zubaidi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
One of the discussions in the fiqh chapter relating to the position of women when praying in congregation with male worshippers, it has been agreed by salaf scholars based on the hadith of the Prophet that the best position of female pilgrims is to be behind. However, it is allowed for the position of female pilgrims to be next to male pilgrims as long as there is a barrier or barrier that blocks it. This certainly does not apply in the Haram mosque of Makkah because the condition is dharurat. But an unnatural scene occurred in the Pondok al-Zaitun mosque, when there was a female makmum behind the imam, while behind the female makmum there was a male worshipper. This research explores the Islamic perspective on the law of women praying in congregation in the back shaf in mosques. The method of study of literature and the Quran is used, with a philosophical approach to science. The results showed that views on women's prayers in mosques varied according to some scholars. After exploring the laws of various schools of jurisprudence, researchers did not find any law that allows women to pray in the front shaf. This study concludes that women's understanding and practice in congregational prayer in mosques must be adapted to the context and view of Islam that is inclusive and full of wisdom.